The Effect Of Contextual Teaching And Learning On Students’ Reading Comprehension - Azan, Muhammad; Sahlan, Sahlan; Alberth, Alberth (Halu Oleo University, 2017)
This paper presents a research to examine whether or there is any significant difference of reading comprehension between low and high vocabulary a chievers taught using CTL approach and those taught using traditional approach, and To describe the students’ perception toward the use of contextual teaching and learning approach. . The participants consisted of 62 students with high and low vocabulary kowleadge . The participants were divided into an experimental group (n = 33) and a control group (n = 29). The the research employed a mixed method (quantititative and qualitative). Standardized reading test and inferential statistical analysis were employed to measure the difference of reading comprehension between students using CTL approac and traditional approach. Then semi structured inteview and intra case analysis were performed to describe students perception toward the use of CTL approach. Results showed that : (1) there is no sigrnificant difference of reading comprehension between low achievers taught using CTL approach and those taught using traditional approach; (2) there is a significant differnce of reading comprehension between high achievers taughtt using CTL approach and those taught using traditional approach; (3) in general, the use of CTL approach in teaching reading was perceived positively by students. The impacts of using this approach were noticeable on the emergence of students’ fun and motivation to learn reading. However the use of this approach was not affective enough to improve the reading comprehension of students with limited vocabularies.